Semileptonic Transition of Tensor χc2(1P) to Ds Meson. (13th October 2014) - Sungu, J. Y.; Sundu, H.; Azizi, K.
Abstract : Taking into account the two-gluon condensate corrections, the transition form factors of the semileptonic χ c 2 → D s l - ν ( l = e, μ ) decay channel are calculated via three-point QCD sum rules. These form factors are used to estimate the decay width of the transition under consideration in both electron and muon channels. The obtained results can be used both in direct search for such decay channels at charm factories and in analysis of the Bc meson decay at LHC.